Educação para o trânsito: sua inserção nas quatro primeiras séries da educação fundamental - Guimarães, Norma Lúcia Bezerra (2001)
Traffic accident is one of the main causes of violent deaths of children between 5 and 14 years of age, and the Traffic Safety Education is one of the alternatives that can effectively improve that situation. Unfortunately, systematic education for traffic safety is not yet a reality in Brazil, despite the Brazilian laws have made it compulsory for Elementary School, High School and College. The main aims of this dissertation are: 1) To join, in a text, the fundamental elements for setting up a Traffic Safety Education program suited to the first four years of Elementary School; and 2) To present, as an example, a Traffic Safety Education program implemented in a Brazilian city, and to show how the program would work if it was based on another pedagogic tendency. In order to achieve those aims, three topics are presented and discussed: 1) Traffic, traffic accidents and their causes; 2) Traffic safety education program for first four years of elementary school, and basic contents inferred from the risky situations commonly faced by children; and 3) Pedagogic tendencies and their characteristics. Finally, an application is presented, In the first phase, it is described the traffic safety education pedagogic tendency for the city of Maceio (State of Alagoas), which is based on the hypothesis of Traditional Liberal pedagogic tendency. In the second phase, the underlying pedagogic tendency is changed from Traditional Liberal to Progressive Libertarian. And then, the resulting pedagogic actions are discussed.